The relationship between Regional Growth and Regional Inequality in EU and transition countries - a Spatial Econometric Approach - Giuseppe Arbia; Laura De Dominicis; Gianfranco Piras (European Regional Science Association (ERSA), 2005)
Is inequality good or bad for growth? This issue, with its important political bearings, has attracted much attention in the past in the economic literature. Starting from the seminal work of Kuznet (1955), in the literature there is some empirical evidence that economies with unequal distribution of income grow faster than those with an even income distribution. Such a belief has been heavily criticised by recent studies, and some contrasting views, supported by empirical evidence, were expressed e.g. by Aghion et al. (1999). Barro (2000) also argues in this direction, but empirically found little overall relation between income inequality on one side and growth rates and investment on the other. The debate, thus, seems still open. In our analysis we aim at investigating whether space and spatial relationships play a significant role in the specification of the relationship between regional inequality and regional growth. In particular, we analyse the case of European Regions, including the transition countries that recently joined the EU. In the empirical analysis, we make use of spatial panel data models, as they let us consider both time-invariant country specific fixed-effects and spatial dependence. By controlling for omitted variables and for spatial dependence we can be more confident that the estimated coefficient measures exactly the impact of inequality on the growth process.
Keywords: 330